Should I stay or should I go : Irregularly somewhere in the middle - Lehtikunnas, Laura (fi=Turun yliopisto|en=University of Turku|, 2018)
Refugees and migration are a great challenge in world politics. The global challenge of refugees and human rights is a complex and broad topic within the international law to which the States are trying to find effective measures and solutions fast. This thesis is about to provide knowledge and better qualified arguments for discussions as well as for sustainable legislation and practices, taking also the process economic point of view into the consideration. This thesis is especially an analysis of the asylum interview´s significance, and its role as a fork on the road of becoming irregular migrant. This research deal with asylum processes among national, regional and international legal frameworks, and clarifies how Finland and Finnish legislation, regulations, policies and practices are positioned into the international legislation and regulations. The research focusses on the role of national and international legislation and practices in creating irregular migrants. Epistemic violence and challenges in linguistic exchanges are of great importance in this thesis. With this research, I will show how the society, consciously or unconsciously, creates a group of people living in a vulnerable situation, and show the importance of the asylum interview in terms of process economy and legal security by bringing together elements from legal dogmatics as well as from sociology of law. As a material I have used mainly primary and secondary sources, mostly law and politics documents. The main purpose is to provide critical, yet constructive and pragmatic views on migration. Pakolaisuus ja maahanmuutto ovat merkittävä ja ajankohtainen haaste maailman politiikassa. Pakolaisuus ja ihmisoikeudet muodostavat globaalisti hyvin monitahoisen ja laajan teeman kansainvälisten oikeuden sisällä, johon valtiot pyrkivät löytämään tehokkaita välineitä ja ratkaisuja nopeasti. Tämä tutkielma tarjoaa tietoa ja ymmärrystä sekä laadukkaampia perusteita keskusteluun, ja myös kestävämmän lainsäädännön ja käytänteiden pohjaksi, ottaen myös prosessi-ekonomiset näkökohdat huomioon. Tämä tutkielma on erityisesti analyysi turvapaikkapuhuttelun merkityksestä ja sen roolista osana polkua kohti paperittomuutta. Tämä tutkielma käsittelee turvapaikkaprosesseja kansallisen, paikallisen ja kansainvälisen lainsäädännön puitteissa ja selventää, miten Suomi ja Suomen lainsäädäntö, säännökset ja politiikka sekä käytänteet asemoituvat kansainvälisessä kentässä. Tutkimus keskittyy kansallisen ja kansainvälisen lainsäädännön ja käytänteiden rooliin paperittomuuden ilmiön muodostamisessa. Episteminen väkivalta sekä haasteet kielellisessä kommunikaatiossa ovat keskeisessä asemassa tässä tutkielmassa. Tällä tutkimuksella osoitan, miten yhteiskunta tiedostaen tai tiedostamatta luo heikossa asemassa olevaa ihmisryhmää, ja osoitan turvapaikkapuhuttelun merkityksen turvapaikkamenettelyssä prosessiekonomian ja oikeusturvan näkökulmasta yhdistäen elementtejä oikeusdogmatiikasta sekä oikeussosiologiasta. Materiaalina olen käyttänyt pääasiallisesti voimassaolevaa lainsäädäntöä ja sitä koskevia valmisteluasiakirjoja sekä poliittisia ja oikeustieteellisiä artikkeleita. Ensisijainen tarkoitus on tuottaa kriittisiä, kuitenkin rakentavia ja pragmaattisia, näkökulmia maahanmuuton haasteisiin.